2020
DOI: 10.1111/1462-2920.14997
|View full text |Cite
|
Sign up to set email alerts
|

Specific proteomic adaptation to distinct environments in Vibrio parahaemolyticus includes significant fluctuations in expression of essential proteins

Abstract: Bacteria constantly experience changes to their external milieu and need to adapt accordingly to ensure their survival. Certain bacteria adapt by means of cellular differentiation, resulting in the development of a specific cell type that is specialized for life in a distinct environment. Furthermore, to understand how bacteria adapt, it is essential to appreciate the significant changes that occur at the proteomic level. By analysing the proteome of our model organism Vibrio parahaemolyticus from distinct env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Only Rauprich et al [32] indicated that the leading edge of P. mirabilis migrating cells was quite ragged in appearance. However, the encroaching swarm fronts of the following strains Serratia liquefaciens MG1 [39], B. subtilis JCM 32,485 [40], Bacillus cereus NCIB 8122 [41], and Vibrio parahaemolyticus RIMD 2,210,633 [42] also resembled finger-like structures migrating outward towards the colony border.…”
Section: Discussionmentioning
confidence: 99%
“…Only Rauprich et al [32] indicated that the leading edge of P. mirabilis migrating cells was quite ragged in appearance. However, the encroaching swarm fronts of the following strains Serratia liquefaciens MG1 [39], B. subtilis JCM 32,485 [40], Bacillus cereus NCIB 8122 [41], and Vibrio parahaemolyticus RIMD 2,210,633 [42] also resembled finger-like structures migrating outward towards the colony border.…”
Section: Discussionmentioning
confidence: 99%
“…Acidophile (pH 0.5 to 5) Efficient efflux system, acid tolerant membrane, proton exclusion and secondary transporters driven by protons [45,46] Halorhodospira halochloris, Thiohalospira alkaliphila, Bacillus firmus, Natronomonas pharaonis Alcaliphile (pH 8.5 to 11) Efficient proton uptake system mediated by antiporters of the membrane, OH-ion [45] Psychrobacter adeliensis, P. aestuarii, P. alimentarius, P aquimaris, P. luti, P glacincola Psychrophile (-10°C-40°C) Synthesis of unsaturated fatty acids to prevent the decrease of membrane fluidity reduces the size of the cell and elevates cellular water in an ordered fashion [47][48][49] Serratia ureilytica Thermophile (20°C-54°C) Modified vegetative cells into resistant structures [50] Available at www.veterinaryworld.org/Vol.17/March-2024/20.pdf by changing into different cell types (swarm cells) to maintain optimal growth and motility [57,58]. This adaptation involves a number of genes involved in their expression and repression.…”
Section: Acidithiobacillus Ferrooxidans Halarchaeum Acidiphilum Metal...mentioning
confidence: 99%
“…The bacteria can also become resistant to antibiotics due to the mutations in their genome or by uptaking foreign DNA (Larsson and Flach 2021). The microbes can also adapt to the changing environmental condition by transforming to different cell types that help the microbes to maintain optimum growth in new environment (Freitas et al 2020). An example of this changing environment adaptability towards the changing surrounding support is reported in Vibrio parahaemolyticus (Freitas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The microbes can also adapt to the changing environmental condition by transforming to different cell types that help the microbes to maintain optimum growth in new environment (Freitas et al 2020). An example of this changing environment adaptability towards the changing surrounding support is reported in Vibrio parahaemolyticus (Freitas et al 2020). In a highly viscous vicinity, the bacteria form a swarmer cell that ensures motility for the process of chemotaxis (Jose and Singh 2020).…”
Section: Introductionmentioning
confidence: 99%